Bootstrap methods in CFT. Issue 4 (8th March 2016) - Rastelli, Leonardo
Abstract : This contribution collects background material and references for the overview talk that was delivered in the 21st European string workshop and 3rd COST MP1210 meeting, 'The String Theory Universe'.